Correlates of Quality of Life in the Family Caregivers of Schizophrenic Patients with Hope - Z. Ghahremani; M. Jafarpoure Alavi; M. Gholam araghi; F. Hosseini (Iran University of Medical Sciences, 2006)
Families of patients with Schizophrenia endure remarkable hardship for coping with their patient's psychotic symptoms and they confront several physical and emotional stresses. Regarding the importance of family's role in supporting patients in community-based services, the present study was conducted to determine correlates of quality of life in the family caregivers of schizophrenic patients with hope in Medical Education Centers, Tehran, 2006.   This correlational study, was carried out on 260 family caregivers of patients with schizophrenia who had been referred to Medical Educational Centres in Tehran. A convenience sampling method was used and the study conducted in April- June in 2006. The data collection tool consisted of demographic questionnaire, Quality of Life Family Version and Miller Hope Scale (MHS). Data were analyzed using SPSS Soft Ware, descriptive statistics, c 2 and Spearman correlation coefficient.   The result, showed that 27.3% of family caregivers had inappropriate quality of life, 64.2% of them had good quality of life and 8.5% of them had very good quality of life. 53.5% of family caregivers had high level of hope, 45% of them had moderate hope and 1.5% had low level of hope. There was a significant direct relationship between quality of life and hope ( c 2 = 56.80, P =0.000 & r =0.679, P=0.000) in the subjects. Quality of life was correlated with economic status ( c 2 = 17.61, P= 0.0001), and education status ( c 2 =15.09, P= 0.020).   In this study regarding the correlation between quality of life and hope, the researchers recommended that using coping strategies may improve quality of life and the level of hope among family care givers of patients with schizophrenia.